Identificación e historia natural de familias botánicas del sendero de downhill en el campus Salache de la Universidad Técnica de Cotopaxi Latacunga- Ecuador. - Zurita Rivera, Evelyn Patricia (2019)
The purpose of this research work is to inventory and describe the botanical families present in the downhill path of the Salache campus of the Technical University of Cotopaxi, located in the contiguous mountain of the university with altitudes between 2.616 and 2.990msnm. And to describe the natural history of the vegetal species and associated fauna itself that serves to elaborate an instrument of basic information (photographic guide) and technical (key of identification) since up to the present time neither studies nor registers exist on the flora of this locality. For this purpose, applied methodologies were used such as the installation of transects for the collection of botanical samples, direct observation, photographic records, identification in the field and in the laboratory. As for the study area, it corresponds to the semi-deciduous forest and shrub of the northern valleys (BmMn01), it is the closest to the characteristics study area. An inventory of 14 families, 22 genus and 22 plant species were obtained from this place, identifying them taxonomically. The most dominant families along the trail were the grasses (Poaceae) which is recorded in 78% of the trail followed by the pineapple family (Bromeliaceae) in 61%, followed by the sunflower family (Asteraceae) with 54%, then the chocho family (Fabaceae) in 53%, and finally the mint family (Lamiaceae) with 51%. With the obtained data in the field and laboratory botanical descriptions are included of each family with their respective photographs is also added ecological data and of interest to people. In addition, the inventory and obtained database from this research contributes as input for publications of the Applied Botanical Herbarium UTCEC, which sponsored this research project; a photographic guide and a scan of the samples that rested in the Herbarium of Technical University of Cotopaxi of 22 registered species is included as an annex.